OPTIMIZING CROSSWORD PUZZLE METHOD TO IMPROVE ENGLISH VOCABULARY MASTERY OF LPD EMPLOYEES - Sumartini, Ni Luh Putu Unix; Meitridwiastiti, Anak Agung Ayu (Linguistik : Jurnal Bahasa dan Sastra, 2022)
This study aims to find out how optimal the application of the crossword puzzle method is to the results of English vocabulary mastery training for LPD (Lembaga Perkreditan Rakyat) employees in Guwang village, Gianyar Regency. LPD employee naturally deal with vocabularies about banking and finance, but they also equipped with technology and information things daily. By mastering information and technology terms for banking and finance fields is considered improving their self-awareness as an LPD employee in this society 5.0. The type of the research is a qualitative case study model using a pre-experimental design by distributing questionnaires and conducting initial interviews regarding information technology terms to 20 employees. Thus the research sample is the LPD employees at the Guwang Pekraman village, Gianyar, which consists of some level of education such as senior high school, vocational school, diploma and university. The research instrument was a crossword puzzle sheet consist of 20 vocabularies related to financial and information technology terms in English. While the research data were analyzed using data analysis techniques with interactive models (Interactive Mode of Analysis). The stages in data analysis are Data Reduction, Data Presentation and Drawing conclusions. Based on the hypothesis testing that has been done, it can be concluded that the use of the crossword puzzle method has an effect on increasing interest in mastering English actively and increasing the self-confidence of employees. The results of the data analysis are 11 people (55%) who only get vocabulary under 10 pieces (Group. A). Those who managed to get a vocabulary of 10 to 15 were as many as 6 (30%) people (Group. B), the remaining 3 people (15%) got results if they were above 15 (Group. C).